2007
DOI: 10.1614/ws-04-178.1
|View full text |Cite
|
Sign up to set email alerts
|

Time and Temperature Requirements for Weed Seed Thermal Death

Abstract: Mortality of weed seeds at temperatures of 39, 42, 46, 50, 60, and 70 C was recorded through time under controlled laboratory conditions similar to those of soil solarization for six weed species: annual sowthistle, barnyardgrass, black nightshade, common purslane, London rocket, and tumble pigweed. Time and temperature requirements for thermal death varied considerably among the species studied. Barnyardgrass, London rocket, and annual sowthistle were more susceptible to heat treatment than black nightshade, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
107
0
7

Year Published

2010
2010
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 106 publications
(121 citation statements)
references
References 19 publications
7
107
0
7
Order By: Relevance
“…The high SS sensitivity of annual weeds such as speedwell, henbit, corn poppy and common sowthistle seems to agree with literature reports, whereas previous statements contrast with strong suppression of common purslane and resistance of amaranth species observed in this study (Candido et al 2008;Dahlquist et al 2007;Stapleton and DeVay 1995). The lesser presence of amaranth species in nonsolarized soil could be explained by the strong competition of Canada thistle; also, the increased amaranth infestation in the plots solarized with the BDF mulch may be attributed to the lower thermal effect of this material.…”
Section: Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…The high SS sensitivity of annual weeds such as speedwell, henbit, corn poppy and common sowthistle seems to agree with literature reports, whereas previous statements contrast with strong suppression of common purslane and resistance of amaranth species observed in this study (Candido et al 2008;Dahlquist et al 2007;Stapleton and DeVay 1995). The lesser presence of amaranth species in nonsolarized soil could be explained by the strong competition of Canada thistle; also, the increased amaranth infestation in the plots solarized with the BDF mulch may be attributed to the lower thermal effect of this material.…”
Section: Resultssupporting
confidence: 92%
“…The time and temperature needed for thermal death of weeds vary considerably among different species, but temperatures above 50°C are generally lethal to some weed seeds (Dahlquist et al 2007). Under appropriate climate conditions, SS can provide an effective and environmentally safe suppression of weeds under field and greenhouse conditions (Elmore 1991;Yaduraju and Mishra 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Water content of seeds decreases with maturation (Bewley and Black 1983) and ripening dandelion seed is presumably sensitive to high temperatures because its water content is higher than in ripe seed. This would be consistent with the studies of imbibed seeds (Egley 1990, Dahlquist et al 2007 which showed that temperatures above 50°C are fatal for seeds of twelve weed species, some of which (Echinochloa crus-galli L. Beauv., Sisymbrium irio L., Sonchus oleraceus L.) are killed within few hours even at temperatures between 40-50°C.…”
Section: Discussionsupporting
confidence: 90%
“…The latter values would be lethal for most seeds and propagules (Dahlquist et al, 2007) and would therefore be an important tool for farmers when clearing a piece of forest for agriculture, as recognised in old documents (de Roxas, 1808). Similar temperatures may be reached in the soil under the 'formiguer' down to a depth of 1-2 cm (Giardina et al, 2000b).…”
mentioning
confidence: 99%